Chiral selectors in CE: Recent developments and applications (2012‐mid 2014). Issue 1 (17th November 2014) - Stavrou, Ioannis J.; Mavroudi, Maria C.; Kapnissi‐Christodoulou, Constantina P.; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> There is a large number of chiral selectors (CSs) that have, over the years, been synthesized and used in electrophoretic enantioseparations. This report highlights the most important CSs applied in CE during the period 2012 to mid‐2014. It is mainly focused on method developments and validations, along with pharmaceutical and biomedical applications. Even though numerous publications have, through the years, reported the utilization of CSs in enantioseparations, only the ones applied in electrophoretic techniques the last approximately three years are demonstrated in this review article. In particular, cyclodextrins, cyclofructants, linear and branched oligo‐ and polysaccharides, antibiotics, and polymeric surfactants are presented, and their advantages, their chiral recognition mechanisms, and their performance are discussed.